Challenging Liberian Attitudes towards Violence against Women - Munala, June (Forced migration review, 2007)
During the 14-year long civil war, Liberia's south-east region witnessed extreme levels of sexual violence. Without action to heighten awareness of the root causes of male violence it will not be possible to unlearn destructive notions of masculinity & machismo. Adapted from the source document.